How past experiences matter: exploring the relationships between children's past math performance with their math-brilliance beliefs and math-related outcomes - Koh, Anne Xiao Ting (Nanyang Technological University, 2022)
The underrepresentation of women in STEM fields has been attributed to the endorsement of field-specific ability beliefs that discourage women from aspiring towards careers in fields that are believed to need brilliance to succeed, a trait believed that males are more likely to possess. Past studies have found how children also have similar field-specific abilities, such as in the subject of math, known as math-brilliance beliefs, influencing their beliefs and math-related outcomes such as their math self-efficacy and interest. However, few studies have explored possible variables that contribute to the endorsement of math-brilliance beliefs, such as their past experiences like past math performance. The present study fills this gap by sampling secondary school students in Singapore who self-reported their math-brilliance beliefs, math self-efficacy and interest, as well as their past math performance, to explore the relationships between these variables. Results revealed that past math performance of girls positively predicted their math self-efficacy and interest, and that math-brilliance beliefs also moderated the strength of the relationship between past math performance of girls in positively predicting their math interest.